Arystoteles czy św. Tomasz z Akwinu? Głębsze rozumienie intelektu - Zaorski, Mariusz (Warszawskie Studia Teologiczne, 2018)
The presented concept of intellect shows the size and innovation of St. Thomas Aquinas. As opposed to Aristotle, St. Thomas explains the nature of intellect more precisely. Aristotle used only one concept in describing form and matter. However, this was not enough to show the existence of intellect a<er de-ath. Only the new idea describing the combination of essence and act of existence discovered by St. Thomas allowed one to understand that intellect and soul do not cease to exist even a<er separating the soul from the body. Furthermore, thanks to St. Thomas Aquinas’ insight Aristotle’s theory of two intellects: form and matter was interpreted correctly. Using the understanding of intellect as an example, we can conclude, the philosophy of Aquinas is more complex. Thomistic philosophy turns out to be crucial in the understanding of Christian anthropology and in its apologetics. The defense of intellect and immortality of the soul based on solid foundations is ne-eded especially today, in the times of moral relativism and the relativism of faith.